Clostridium difficile infection in children: a comprehensive review. (3rd June 2013) - Pant, Chaitanya; Deshpande, Abhishek; Altaf, Muhammad A.; Minocha, Anil; Sferra, Thomas J.
Abstract: Objective: To provide a comprehensive review of the literature relating to Clostridium difficile ( C. difficile ) infection (CDI) in the pediatric population. Methods: Two investigators conducted independent searches of PubMed, Web of Science, and Scopus until March 31st, 2013. All databases were searched using the terms ' Clostridium difficile infection ', ' Clostridium difficile associated diarrhea ' 'antibiotic associated diarrhea', ' C. difficile ', in combination with 'pediatric' and 'paediatric'. Articles which discussed pediatric CDI were reviewed and relevant cross references also read and evaluated for inclusion. Selection bias could be a possible limitation of this approach. Findings: There is strong evidence for an increased incidence of pediatric CDI. Increasingly, the infection is being acquired from the community, often without a preceding history of antibiotic use. The severity of the disease has remained unchanged. Several medical conditions may be associated with the development of pediatric CDI. Infection prevention and control with antimicrobial stewardship are of paramount importance. It is important to consider the age of the child while testing for CDI. Traditional therapy with metronidazole or vancomycin remains the mainstay of treatment. Newer antibiotics such as fidaxomicin appear promising especially for the treatment of recurrent infection. Conservative surgical options may be a life-saving measure in severe or fulminant cases. Conclusions: Pediatric providers should be cognizant of the increased incidence of CDI in children. Early and judicious testing coupled with the timely institution of therapy will help to secure better outcomes for this disease.